Web-based dyscalculia pre-screening tool / Nur Syafeenaz Md Naser - Md Naser, Nur Syafeenaz (2021)
The aim for this research is to design and develop a web-based dyscalculia pre-screening tool that could perform dyscalculia pre-screening for children aged 5 to 8. ADDIE Model has been utilized as the methodology of this study. The ADDIE Model consists of five phases including analysis, design, development, implementation, and evaluation. Mayer’s principle has been utilized as a guideline in designing this system. Few principles from Mayer’s principle was adapted during the design which are multimedia principles, spatial contiguity principle, and personalization principles. Functionality test and user experience test were conducted during the study to evaluate the system. Functionality Testing was conducted to verify that all modules in the system function effectively and efficiently. The result from the UX Testing indicates that most of the users agree that the system is useful, effective, interesting for children, and reliable. It is hoped that, by using this system, the parents and teachers would be able to perform early screening and detect whether their children are having difficulties in performing simple mathematical functions as early as possible. Keywords: Mayer’s Principles, ADDIE Model.